The Improvement of Hyperglycemia after RYGB Surgery in Diabetic Rats Is Related to Elevated Hypothalamus GLP-1 Receptor Expression - Jazyra Zynat; Yuyu Guo; Yingli Lu; Dongping Lin (International Journal of Endocrinology)
Objectives. This study aimed to explore the expression of GLP-1 receptor in hypothalamus and gastrointestinal tissues after Roux-en-Y gastric bypass (RYGB) surgery in diabetic rats. Methods. Male 12-week-old Wistar rats (control) and Goto-Kakizaki rats (diabetic) were randomly divided into two groups, respectively: control sham surgery group (C), control RYGB group (C + R), diabetic sham surgery group (D), and diabetic RYGB group (D + R). Body weight and blood glucose were monitored before and after surgery every week. Eight weeks after surgery, all rats were sacrificed and the serum fasting GLP-1 concentrations were measured by ELISA. GLP-1R and DPP-4 expression in hypothalamus and ileum were measured by RT-PCR. Results. The body weight and fasting/random blood glucose in the D + R group decreased significantly compared with the D group (P<0.05). Serum GLP-1 levels in diabetic rats treated with RYGB were higher than the corresponding sham surgery rats. The expression of GLP-1R of hypothalamus in RYGB-treated diabetic rats was significantly higher than those of the sham surgery diabetic rats and both control group rats (P<0.05). We found a negative correlation between hypothalamus GLP-1R mRNA and blood glucose level. No significant difference was seen in ileum GLP-1R and DPP-4 expression among all groups. Conclusions. RYGB efficiently promoted serum GLP-1 levels and the expression of GLP-1 receptor in the hypothalamus in diabetic rats. These data suggest that the hypothalamus GLP-1R may play an important role in the GLP-1 system for improving glucose homeostasis after reconstruction of the gastrointestinal tract.